2014
DOI: 10.1186/1465-9921-15-71
|View full text |Cite
|
Sign up to set email alerts
|

Rac2 is involved in bleomycin-induced lung inflammation leading to pulmonary fibrosis

Abstract: BackgroundPulmonary fibrotic diseases induce significant morbidity and mortality, for which there are limited therapeutic options available. Rac2, a ras-related guanosine triphosphatase expressed mainly in hematopoietic cells, is a crucial molecule regulating a diversity of mast cell, macrophage, and neutrophil functions. All these cell types have been implicated in the development of pulmonary fibrosis in a variety of animal models. For the studies described here we hypothesized that Rac2 deficiency protects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
10
23
1
Order By: Relevance
“…In this study, we first evaluated the effects of salidroside on BLM-induced lung injuries by examining the histological changes in rats. Our data in keeping with previous studies (Arizmendi et al 2014;Della Latta et al 2015) showed a significant structure distortion of lung tissues in rats challenged with BLM. Abnormal infiltration of inflammatory cells and overproduction of TNFα and IL-6 as well as collagens were presented in BLM-treated lungs.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we first evaluated the effects of salidroside on BLM-induced lung injuries by examining the histological changes in rats. Our data in keeping with previous studies (Arizmendi et al 2014;Della Latta et al 2015) showed a significant structure distortion of lung tissues in rats challenged with BLM. Abnormal infiltration of inflammatory cells and overproduction of TNFα and IL-6 as well as collagens were presented in BLM-treated lungs.…”
Section: Discussionsupporting
confidence: 93%
“…Bleomycin (BLE) is a medicine applied to treat a variety of human diseases. But it has severe side effects of inducing pneumonitis and fibrosis [32]. Therefore, BLE is usually used to establish acute lung injury model in vivo [33].…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced effect of α7 nAChR agonist GTS-21 on TGF-β-induced expression of Fstl1, Acta2 and Col1a1 was diminished by deletion of Chrna7 (Figures 11C-F). It takes approximately 3 wks to establish a mouse model of BLM-induced lung fibrosis (59,60). The mice challenged with high-dose bleomycin usually died after 7 d; therefore we had to euthanize mice by 7 d. The first week is the early BLM-induced lung fibrosis mouse model.…”
Section: Deletion Of Chrna7 Abolishes Tgf-a1-induced Profibrotic Genementioning
confidence: 99%